IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 16 TEMIANG KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - maisyarah maisyarah; lazim lazim; Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve the results of learning mathematics Elementary School fourth grade students 16 Temiang Bukit Batu subdistrict Bengkalis with Application of Cooperative Learning Model Student Teams Achievement Division (Stad). Results of this study was obtained from observations of the activities of teachers and students during the learning process and student achievement test. This research is a form of action research consisted of two cycles. An increase in activity of teachers and students at each cycle using the Cooperative Learning Model Student Teams Achievement Division (Stad). In the first cycle replicates the average value replications 65.56, students who completed as many as 9 people (50%), and incomplete 9 people (50%). While in the second cycle the average value increased by 6:11 points to 71.67 with completeness 17 students (94.44%), and students who do not complete 1 (5:56%). From the results of this study concluded that the Application of Cooperative Learning Model Student Teams Achievement Division (STAD) can improve the results of learning mathematics Elementary School fourth grade students 16 Temiang Bukit Batu subdistrict Bengkalis.Keywords : Cooperative Learning Type of Student Teams Achievement Division (Stad), Mathematics Learning Outcomes and PTK